Tawny Crazy Ant (previously known as Caribbean crazy ant) Nylanderia (formerly Paratrechina) fulva (Mayr) (Insecta: Hymenoptera: Formicidae: Formicinae) - Shweta Sharma; John Warner; Rudolf H. Scheffrahn (EDIS)
Nylanderia fulva is part of a group of ants referred to as “crazy ants” due to their quick and erratic movements. It has been reported from 27 counties of Florida and 27 counties of Texas, as well as from Louisiana, Mississippi, Alabama, and Georgia. Huge number of workers in infested areas can make human activities uncomfortable and difficult. They can infest sidewalks, buildings and gardens, and damage phone lines, air conditioning units and computers. They have killed honey bee larvae and used the hives as their nests, and are even displacing red imported fire ants where the two populations overlap in Texas. This 5-page fact sheet was written by Shweta Sharma, John Warner, and Rudolph H. Scheffrahn, and published by the UF Department of Entomology and Nematology, December 2014. (Photo: Lyle Buss, UF/IFAS)